2001
DOI: 10.1002/jsfa.974
|View full text |Cite
|
Sign up to set email alerts
|

The allergenicity of ovomucoid and the effect of its elimination from hen's egg white

Abstract: In order to remove the ovomucoid from hen's egg white, chitin and hydrazide polystyrene beads were used as af®nity ligands with 8.9 and 7.1 mg trypsin g À1 ligand respectively. Ovomucoid was successfully depleted using the trypsin af®nity column without hydrolysation of the other egg white constituents. The components of the egg white were puri®ed by high-performance liquid chromatography, and then the allergenicity of each of these components was compared with that of pooled human serum derived from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The contradictory results on egg white allergenicity may, therefore, be attributable to several aspects: (a) differing degrees of purity of individual protein fractions and antibody sources, (b) using sera from either humans with egg allergy or antibodies raised from experimental animals, or (c) different routes of administration (injection or oral administration). For example, commercially pure OA, which is generally accepted as the most allergenic protein and extensively studied as a model allergen, has been found to contain OVM as an impurity, which led to an overestimation of the dominance of OA as the major egg white allergen ( , ). Furthermore, many researchers have used rabbit or mouse antibodies for studies of egg protein allergenicity and antigenicity ( ).…”
Section: Introductionmentioning
confidence: 99%
“…The contradictory results on egg white allergenicity may, therefore, be attributable to several aspects: (a) differing degrees of purity of individual protein fractions and antibody sources, (b) using sera from either humans with egg allergy or antibodies raised from experimental animals, or (c) different routes of administration (injection or oral administration). For example, commercially pure OA, which is generally accepted as the most allergenic protein and extensively studied as a model allergen, has been found to contain OVM as an impurity, which led to an overestimation of the dominance of OA as the major egg white allergen ( , ). Furthermore, many researchers have used rabbit or mouse antibodies for studies of egg protein allergenicity and antigenicity ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al determined the purities of two ovalbumin samples, grade V and II, using SDS-PAGE on the basis of gel image analysis; the values were 76.0 and 38.0%, respectively (11). Mine et al also reported that there was approximately 6.7% impurity in the commercially available ovalbumin as calculated from the HPLC profile, and the impurity was identified as ovomucoid by analyzing with SDS-PAGE and amino acid sequencing (12). In the present work, using mAbs generated by commercially available ovalbumin, we have established an ELISA kit specific for ovomucoid from hen's egg white.…”
Section: Discussionmentioning
confidence: 92%
“…In the previous studies, several methods were used to quantitatively analyze the amount of ovomucoid, including SDS-PAGE, Western blot, analysis of high-performance liquid chromatography (HPLC) profile, and sandwich enzyme-linked immunosorbent assay (ELISA) (3,8,(10)(11)(12), but the sensitivity and/or specificity were still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Protein fractions extracted from the dough were separated by trypsin-immobilized affinity column chromatography (Mine & Zhang, 2001). The adsorbed substances were eluted by the linear gradient of pH 6.5 to 7.5 in 1.0 M phosphate buffer.…”
Section: Separation Of Proteins By Affinity Chromatographymentioning
confidence: 99%